THE ESSENCE, GOALS AND FUNCTIONS OF PUBLIC GOVERNANCE IN THE HEALTHCARE SECTOR - Radchenko, Oleksandr; Dakal Аllа (Public Management and Policy, 2026)
The article provides a theoretical and applied interpretation of the essence of public governance in the healthcare sector through the substantiation of its goals and functions as interrelated elements of a coherent public policy system. The authors emphasize that the complexity of organizing the work lies in the need to coordinate and simultaneously work with medical care, prevention, social determinants, behavioral and psychological factors, as well as with the data obtained and the institutional capacity of the system. International WHO documents were used to clarify the content of the categories “health”, “primary health care” and “health promotion” as basic semantic guidelines. It is argued that the essence of public governance in healthcare is determined by the dual nature of this domain, where the authoritative role of the state as a guarantor of rights, standards and patient safety is combined with a service-oriented logic focused on human needs and measurable outcomes of public decisions. The goals of public governance in healthcare are interpreted as multidimensional priorities covering the implementation of the right to health, equitable access to services, improvement of quality and patient safety, financial sustainability, institutional capacity, and resilience to crises in the context of war-related and pandemic risks. Based on a synthesis of scholarly approaches, an integrated functional model of healthcare governance is proposed, comprising regulatory and legal, institutional and organizational, strategic, financial and economic, information and analytical, quality and patient safety, preventive and public health, crisis and adaptive, as well as communicative and partnership functions. The article demonstrates that governance effectiveness depends not on declarative goal-setting but on functional decomposition of goals, availability of instruments and enforceable accountability; digital transformation should be treated as a foundation for governability and transparency, while partnerships with communities and non-state actors are a prerequisite for policy legitimacy and system resilience. The conclusion substantiates that an integrated view of the essence, goals and functions of public governance in healthcare provides a conceptual basis for consistent reforms capable of ensuring social equity, high-quality services and crisis readiness.